2009
DOI: 10.1111/j.1600-0625.2009.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Tattooing of skin results in transportation and light‐induced decomposition of tattoo pigments – a first quantification in vivo using a mouse model

Abstract: Millions of people are tattooed with inks that contain azo pigments. The pigments contained in tattoo inks are manufactured for other uses with no established history of safe use in humans and are injected into the skin at high densities (2.5 mg/cm(2)). Tattoo pigments disseminate after tattooing throughout the human body and although some may photodecompose at the injection site by solar or laser light exposure, the extent of transport or photodecomposition under in vivo conditions remains currently unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(106 citation statements)
references
References 34 publications
1
101
1
3
Order By: Relevance
“…In all these cases, the migration of tattoo pigments via lymphatic drainage was initially considered as evidence for metastatic tumors until proper histopathological examination. Meanwhile, the transportation of tattoo inks, admixtures and impurities from the skin to the lymph nodes is a well-known fact [3,8,50]. Tattooists often also tattoo into pre-existing nevi and pigmented lesions, thus impeding a correct clinical and dermatoscopic evaluation [51,52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all these cases, the migration of tattoo pigments via lymphatic drainage was initially considered as evidence for metastatic tumors until proper histopathological examination. Meanwhile, the transportation of tattoo inks, admixtures and impurities from the skin to the lymph nodes is a well-known fact [3,8,50]. Tattooists often also tattoo into pre-existing nevi and pigmented lesions, thus impeding a correct clinical and dermatoscopic evaluation [51,52].…”
Section: Resultsmentioning
confidence: 99%
“…the staining of consumer products) with no established history of safe use in humans. In addition, such pigments can be decomposed during light exposure into hazardous aromatic amines and can be disseminated throughout the human body [3]. Many pigments and, consequently, the decomposition products have been found in the lymph nodes [4,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of tattoo pigment in the skin is not stationary. In a study of mice tattooed with Pigment Red 22, Engel et al [26] showed that after 42 days the amount of pigment in the skin had decreased by 32%. This was done by quantitatively extracting the pigment at different times after tattooing.…”
Section: Discussionmentioning
confidence: 99%
“…This was done by quantitatively extracting the pigment at different times after tattooing. Furthermore, clearance of the skin from tattoo pigment was shown to depend on light exposure and photodecomposition [26] . Thus, distribution of tattoo pigment from skin to the regional lymph nodes is significant and occurs dynamically, especially during the first few weeks after tattooing when systemic distribution might occur [27] .…”
Section: Discussionmentioning
confidence: 99%
“…W analizie, której dokonali niemieccy naukowcy, badano tusze do tatuażu, które zostały wstrzyknięte pod skórę myszy. Dowiedziono, że 32% barwnika zniknęło 42 dni po wstrzyknięciu; większe cząsteczki uległy kumulacji w wę-złach chłonnych, a nanocząsteczki prawdopodobnie dostały się do krwiobiegu i zostały rozprowadzone po organizmie [13]. Potwierdza to eksperyment przeprowadzony w Chinach w 2009 roku, polegający na iniekcji nanocząsteczek i mikrocząsteczek srebra pod skórę szczurów.…”
Section: Wprowadzenieunclassified